Research on World City Evaluation System Based on the Concept of Regional Space "Flow". Issue 5 (May 2019) - Qi, Luhui; Zeng, Fanlong; Chen, Lixin
Abstract: In 2012, the United Nations published the white paper "Big Data for Development: Challenges and Opportunities", pointing out that the "big data era" has arrived. The concept of "data stream" will continue to profoundly affect all aspects of the global economy, society and life. The "vertical" relationship between cities in the traditional urban hierarchy is gradually replaced by the "horizontal" relationship in the urban network system. As the concept of "big data" gradually moves from theory to practice, the world city evaluation system is based on the evidence of air passenger flow, port logistics, Internet information flow data, enterprise top 100 multinational corporations' enterprise layout and scale data, and high-end productive service industry. Data research, further reorienting the path of urban competitive advantage from the perspective of world urban network, proposes the strategy of urban competitiveness improvement under the background of the world urban network system, which undoubtedly promotes the refinement of China's big data urban and rural planning to the planning process. Scientific advancement provides guarantee and technical support for scientific and rational planning results.